Projekt wdrożenia zrównoważonej karty wyników jako innowacji w systemie zarządzania strategicznego na przykładzie firmy zarządzanej przez projekty - Drozd, Konrad (The Project of BSC Implementation as an Innovation in the Strategic Management System on the Example of a Project Managed Company, 2006)
Balanced Scorecard is useful in working out a strategy by defining business aims of a company. It also supports implementation of the strategy, currently modifying and adjusting it to changing conditions of environment. It also serves for measuring the effectiveness of realized actions. The example of the studied company confirms the complex character of Balanced Scorecard as a tool of management incorporating the whole company and integrated with other systems of management in a firm. The card is particulary efficient as an element of strategic management i.e. in the sphere of verification of company's strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 59-66